THE USE OF SCIENTIFIC APPROACH IN TEACHING ENGLISH AS A FOREIGN LANGUAGE IN SMPN I JAKARTA - Muh Imam Shofwan (Universitas Islam Nahdlatul Ulama Jepara)
Since the first time of curriculum 2013 has been launched by the Ministry of Education and Culture for elementary and high school, it becomes newsworthy and important for education development in Indonesia. This analysis aims to describe: (1) How is application of scientific approach in language teaching, (2) The teachers?? and students?? role in the classroom, and (3) Students?? English language improvement in their classroom. Qualitative research method is used to describe the whole phenomena in the classroom. The source of this case study comes from observing events and documents, while observation and field note supported in collecting the data. The use of video recording also helps the researcher capturing the whole detail information of the teaching process. The finding shows that: (1) the scientific approach is applied by using five principles steps: observing, questioning, experimenting, associating and networking. (2) The Teacher has role as a facilitator while students become subject of education (students?? center). (3) English Students improve more communicative and expressive. In conclusion, the scientific approach is appropriate and gives impact in teaching English. Keywords: scientific approach, language teaching, language development